Stratifications, fragmentations and dispersions: bibliographical notes for a reasoned history of the Library of Liceo Classico and Musicale «F. Petrarca» in Arezzo - Milighetti, Maria Chiara (Bibliothecae.it, 2023)
This essay traces back the genesis, the bibliographic stratification and the history of the Library of Liceo Classico and Musicale «F. Petrarca», in Arezzo, starting from the constitution of its original core, attributable to the Library of the Jesuit College, founded in 1687. A complete survey of this first nucleus, now kept in the Library of the «City of Arezzo» was carried out thanks to ex libris and ownership notes. An attempt was therefore made, within this nucleus, to isolate the main donors (Francesco Redi (1626-1697) e Anton Maria Bonucci (1651-1728)). The library subsequently passed to the Vallombrosani (1773) and then to the Scolopi (1816), enriching itself with new entrances but it was also subjected to a slow dispersion due to the Grand Ducal and Napoleonic suppressions of the religious orders. Finally the original nucleus of the Jesuits passed to the Library of Royal Convitto «Vittorio Emanuele II» and from there, in the 1980s, to the Library of the «City of Arezzo». However, an ancient nucleus still survives in the current Library of Liceo «F. Petrarca», a mapping of which is here provided.